PENGEMBANGAN MEDIA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN SUBTEMA INDAHNYA KERAGAMAN BUDAYA NEGERIKU BERBASIS VIDEO PROSHOW - Laely Dwi Astutik; Rasimin Rasimin; Abdul Ghoni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
A learning media is very essential in the learning process since it aims to improve the students’ achievement and ability to understand the subject. One of the learning media is a video processed from Proshow application. This study aimed to develop a video proshow-based learning media for civic education because it was very necessary to improve the students’ achievement. This study used a research and development approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data were collected through observation, questionnaires, and interviews. The results showed that the product of video proshow-based learning media: (1) was necessary to facilitate the learning of Civic Education in order to improve students’ learning achievement, (2) the development of the learning media was considered feasible by a team of media experts and material experts (3) the video proshow-based learning media effectively improved the students’ achievement, which was showed by the results of small group trials for 88.09% and large group trials for 92.86%.